Fiber Optic Video Transmission : the Complete Guide. - Goff, David (Taylor and Francis, 2013)
Fiber Optic Video Transmission: The Complete Guide is the only comprehensive reference to the techniques and hardware required to transmit video signals over optical fiber. As the broadcast industry moves to HDTV and enhanced television standards become the norm, fiber will become the medium of choice for video transmission, and this book is the essential guide to transmitting video over fiber optic cables. From the most basic video signal to complex multi-channel high definition video, this book details the methods of encoding video signals (including AM, FM, and.